ANALISA PENGARUH KOMPETENSI PROFESIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA DI SMP NEGERI KECAMATAN KEDUNGWUNI KABUPATEN PEKALONGAN - Nur Aminah, 12.5202.0114 (Jurnal Mahasiswa Pasca Sarjana, 2014)
From this aims to ditermine the effect of professional kompetence (X1) to work kepuasan (Y1), Organizational commitment (X2) on job satisfaction (Y1), professional competence (X1) to kinerjaguru (Y2), organizational commitment (X2) on the performance teacher (Y2) and job satisfaction on teacher performance (Y2) are mediated by job satisfaction. The population in this study was a Junior High School teachers sekecamatan Kedungwuni Pekalongan in 2014, including a number of 100 respondents and population studies. The method of analysis used qualitative and quantitative methods. Quantitative analysis is performed using multiple regression testing and test hypotheses on the significance set at 5%. To analyze the models with SPSS 19.0. From the results of this study showed that no significant influence of professional competence, then it implies that job satisfaction does not mediate the professional competence of the teachers performance. The organizational commitment both directly and indirectly positive and significant effect on job satisfaction and teacher performance. The results of this study can be used by subsequent researchers as reference material in the field of Science studies the like. Keywords : Professional Competence, Organizational Commitment, Job Satisfaction and performance